Supply chain best practices – identification and categorisation of measures and benefits - Cuthbertson, R; Piotrowicz, W (Emerald, 2008)
Purpose – This research aims to identify, categorise and compare supply chain measures and benefits listed in literature-based case studies that were named as "best practices". Design/methodology/approach – The research applies iterative triangulation which is a method used to build theories from existing case studies. Selected case studies collected by project partners are used as a source of secondary data. The paper applies various approaches to classifying supply chains as well as identifying the difference between measures proposed in the literature and those used by case companies. Findings – The analysis of the selected sample of cases indicated that the most common measures were related to economic aspects and to operational level activities. There is a lack of shared supply chain measures at the inter-organizational level, while social and environmental aspects are largely ignored. Originality/value – The majority of the measures identified in the collected cases were economic (relating to cost, time, quality and customer). Metrics at an operational level dominate, while supply chain metrics are hardly used. Findings indicate that current performance measurement approaches do not generally include social and environmental issues, which are becoming increasingly important in business.